The effects of nanoparticle drug loading on the pharmacokinetics of anticancer agents. (February 2015) - Petschauer, Jennifer S; Madden, Andrew J; Kirschbrown, Whitney P; Song, Gina; Zamboni, William C
Major advances in carrier-mediated agents, which include nanoparticles, nanosomes and conjugates, have revolutionized drug delivery capabilities over the past decade. While providing numerous advantages, such as greater solubility, duration of exposure and delivery to the site of action over their small-molecule counterparts, there is substantial variability in systemic clearance and distribution, tumor delivery and pharmacologic effects (efficacy and toxicity) of these agents. This review provides an overview of factors that affect the pharmacokinetics and pharmacodynamics of carrier-mediated agents in preclinical models and patients.